Potensi Akses yang Dimiliki Rumahtangga terhadap Pemanfaatan Aktual Pelayanan Kontrasepsi - Wenny Artanty, Djaswadi Dasuki, Nawi Ng (Fakultas Kedokteran Universitas Gadjah Mada, 2010)
Background: Difference in social economic influenced the inequity in fulfilling health needs. The goal of health development in Indonesia increased awareness, desire, and capability to make the healthness. Everyone had equal right to obtain health services.Objective: To know the influence of household’s potential access to actual access in utilizing contraceptive services.Method: This study was an observational research using cross sectional approach. It used secondary data from Sakerti 2000 result. The sample consisted of 2233 household from Central Java province. Bivariable analysis used chi-square test and multivariable analysis used logistic Regression test with 0,05 significant level.Result: The factors influencing household’s potential access to actual access of contraceptive services was household who had more than 5 members and owner of health assurance. The household who had more than 5 member and owner of health assurance had 1,7 and 1,5 time more access to contraceptive services than those who had less than 5 members and had not owner of health assurance.Conclusion: Household who had more than 5 members and owner of health assurance were potential access in utilizing contraceptive services. The social structure was not a barrier in utilizing contraceptive services.Keywords : potential access, actual access, household, contraceptive services